Influence of rumen bypass fat fed in a range supplement on the performance of cows and calves grazing bluestem range - Corah, L.; Cochran, B.; Harmon, D.; Goehring, T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Adding rumen bypass fat to a range supplement reproductive characteristics, cow weight and condition performance during a 43-day postpartum feeding period.
Keywords: Beef; Rumen; Performance; Bluestem